Digital Technology and Artificial Intelligence: New Paradigms and Trends in Environmental Design - Zhang, Jiachuan; Jia, Zhipeng (International Journal of Social Sciences and Public Administration, 2025)
With the rapid evolution of information technology, digital process and artificial intelligence (AI) are becoming decisive forces in the innovation of environmental design discipline. This paper examines how these advances have transformed the core mechanisms of environmental design practice, from the early days of computer-aided design (CAD) and building information modeling (BIM) to the latest machine learning strategies and the use of intelligent design platforms, revealing their significant contribution to improving design execution efficiency and optimization quality. As well as catalyzing environmentally friendly sustainability and user experience innovation. At the same time, this paper also evaluates the current technology implementation obstacles, including security concerns, regulatory constraints and other aspects of the shackles, and carries out strategic foresight on the potential development prospects.